2007
DOI: 10.1038/sj.jid.5700842
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Anti-TNFα Treatment Restores Diabetes-Impaired Skin Repair in ob/ob Mice by Inactivation of Macrophages

Abstract: To date, diabetes-associated skin ulcerations represent a therapeutic problem of clinical importance. The insulin-resistant type II diabetic phenotype is functionally connected to obesity in rodent models of metabolic syndrome through the release of inflammatory mediators from adipose tissue. Here, we used the impaired wound-healing process in obese/obese (ob/ob) mice to investigate the impact of obesity-mediated systemic inflammation on cutaneous wound-healing processes. Systemic administration of neutralizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 44 publications
8
121
1
Order By: Relevance
“…Studies have found that manipulating the phenotype of endogenous macrophages may be a promising therapeutic option for improving tissue repair. 28,29 In nondiabetic mice, the M1/M2 ratio peaked at day 3 and returned to baseline levels at day 10, suggesting progression to the proliferative phase of healing. In contrast, and in similarity with the proinflammatory cytokine profile, the baseline M1/M2 ratio was increased in WT diabetic mice and in NK1RKO and TAC1KO mice.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have found that manipulating the phenotype of endogenous macrophages may be a promising therapeutic option for improving tissue repair. 28,29 In nondiabetic mice, the M1/M2 ratio peaked at day 3 and returned to baseline levels at day 10, suggesting progression to the proliferative phase of healing. In contrast, and in similarity with the proinflammatory cytokine profile, the baseline M1/M2 ratio was increased in WT diabetic mice and in NK1RKO and TAC1KO mice.…”
Section: Discussionmentioning
confidence: 96%
“…8 Imbalance in the M1/M2 ratio has been associated with cardiovascular diseases such as atherosclerosis, 9 metabolism-associated diseases such as diabetes and metabolic syndrome, 10 and autoimmune diseases such as multiple sclerosis, 11 systemic lupus erythematosus, 12 Crohn's disease 13 and rheumatoid arthritis. Persistence of M1 macrophages in the local inflammatory response can also prevent the resolution of inflammation in several chronic skin diseases, such as diabetes-associated skin ulcerations, 14 chronic venous ulcers, 15 and atopic dermatitis. 16 Targeting M1 macrophages during chronic inflammation could therefore be a promising intervention strategy to correct an imbalance between M1 and M2 macrophages, thus promoting the resolution of chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 This reduced expression of alternatively activated macrophage markers is comparable with observations of an increased M1/M2 ratio in DB wounds of humans and mice. [22][23][24][25] Because neutrophils and macrophages play both proinflammatory and anti-inflammatory roles during the course of normal wound healing, it will be important to more fully characterize the functional and migrational time course of these cells in the DB wound.Two chemoattractants, Pf4 and CXCL2 (MIP-2), were expressed at higher levels in DB wounds. Pf4 was higher on postwounding day 5, and CXCL2 was higher on day 7.…”
mentioning
confidence: 99%